Reduction of energy consumption and GHGs emission in investment casting process by application of a new casting method - Dai, Xiaojun J.; Jolly, Mark R.; Zhang, Binxu (Cranfield University, 2012)
In conventional investment casting process of aluminium alloys for the application of the aerospace industry, to assure the quality of the final casting, usually the foundry uses large runner system which results in low yield, high energy consumption and high GHGs emission. In one case of this investigation, the yield is between 5 ~ 10% which means that the current casting process wastes large amount of energy and generates lots of scraps. By applying a new casting method, the bulky runner system and the melting/holding time are significantly reduced, the quality of the casting is improved, and in the meantime the related energy consumption and GHGs emission are significantly decreased. In the investigation, the energy efficiencies and GHGs emission between the current and traditional processes are calculated and compared.